Novel Grafis: Studi Awal Tentang Istilah dan Bentuk - Mohammad Hadid (Ars: Jurnal Seni Rupa dan Desain, 2012)
This article would like to begin a short studyon the term ‘graphic novel’. As we can see, the termis problematic. Most arguments shaped around‘graphic novel’ clearly show that the works havebeen regarded as a part of literature, while theothers have been considered the term as a formof sequential art which has lengthened story. Theaim of this article, then, is to deconstruct the term‘graphic novel’ by pointing out the weaknesses, boththrough the meaning of the term and also by meansof the discourses that have been strengthened withsome episteme built with the essence to justify themeaning of graphic novel amidst the discourses ofsequential art